Evaluation of the Effect of a Step Change in Piezo Actuator Structure on Vibration Reduction Level in Plates - Jerzy WICIAK; Roman TROJANOWSKI (Archives of Acoustics)
This paper presents numerical analyses and a physical experiment on efficiency of different shapes and material composition of piezo actuators on vibration reduction. For this purpose numerical models of a plate clamped on all sides with piezo actuators attached were developed. The elements used were either standard homogeneous elements or the proposed two-part elements with different material composition for inner and outer part of piezo ceramic. Numerical analyses were performed using ANSYS software.